2008
DOI: 10.2136/vzj2007.0070
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Modeling of Carbon Tetrachloride Migration at the Hanford Site Using the STOMP Simulator

Abstract: A: DNAPL, dense nonaqueous phase liquid; FP, Fortran preprocessor; NAPL, nonaqueous phase liquid; PTF, pedotransfer function; SMS, similar-media scaling; SVE, soil vapor extraction. S S : V Z M Numerical simula on has been applied in support of the U.S. Department of Energy's eff orts to characterize the nature and distribu on of CCl 4 contamina on in the deep vadose zone at the Hanford site, near Richland, WA. Three-dimensional simula ons were executed using layered and heterogeneous distribu ons of soil prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…As numerical models are becoming much more efficient, comprehensive, and numerically accurate, their application to a large number of theoretical and practical problems is becoming increasingly widespread. This is true not just for the HYDRUS models but also for other models addressing various soil, hydrologic and environmental science, and engineering problems such as the TOUGH models (Finsterle et al, 2008), STOMP (White et al, 2008), SWAP (van Dam et al, 2008), VS2DI (Healy, 2008), and many other models as discussed by Vereecken et al (2016). As we noted earlier in our 2008 paper (Šimůnek et al, 2008b), we believe that these various models and modeling tools have served, and will continue to serve, an extremely important role in vadose zone research.…”
Section: Discussionmentioning
confidence: 99%
“…As numerical models are becoming much more efficient, comprehensive, and numerically accurate, their application to a large number of theoretical and practical problems is becoming increasingly widespread. This is true not just for the HYDRUS models but also for other models addressing various soil, hydrologic and environmental science, and engineering problems such as the TOUGH models (Finsterle et al, 2008), STOMP (White et al, 2008), SWAP (van Dam et al, 2008), VS2DI (Healy, 2008), and many other models as discussed by Vereecken et al (2016). As we noted earlier in our 2008 paper (Šimůnek et al, 2008b), we believe that these various models and modeling tools have served, and will continue to serve, an extremely important role in vadose zone research.…”
Section: Discussionmentioning
confidence: 99%
“…Liquid CT was previously disposed at the surface and resulted in a CT distribution within the approximately 80 m thick vadose zone and the underlying groundwater (Department of Energy [DOE] 2007). Numerical simulations have indicated that the water added to the vadose zone during waste disposal operations has substantially drained such that moisture conditions have reverted back to near the initial conditions except for the high silt zones of the vadose zone (Oostrom et al 2007;White et al 2008). Operational data suggest that SVE has been effective in the permeable formations and that residual contamination in the low-permeability Cold Creek unit (CCU) will be the primary contaminant source in the vadose zone over the long term.…”
Section: Methodsmentioning
confidence: 99%
“…For a field-scale reactive transport model with explicit representation of geologic heterogeneity on a fine grid, the number of grid cells could be very large [e.g. millions (White et al, 2008)]. Therefore, computational demands of the direct coupling approach may be prohibitive.…”
Section: Coupling the Constraint-based Model With Reactive Transport mentioning
confidence: 99%